El silencio administrativo negativo en el recurso de apelación y sus efectos. - Bautista Quintana, Linda Michelle (2023)
In the Ecuadorian legislation, the COA implements the positive administrative silence when a citizen submits a petition, and this is not answered in the time determined by law. However, within the administrative procedure, in the appeal, the negative administrative silence is configured, both when the deadline for the resolution of the appeal is not met and when the term is not met when the suspension of the administrative act is presented. During the course of this qualitative approach research, it was identified that several legal professionals agreed in establishing that the rights violated due to the tacit refusal in the appeal are different from the general due process, and the objective was to identify whether the tacit refusal in the appeal violates the rights of the applicant. The research is of non-experimental design, and the methods applied are based on the inductive method, doctrinal legal method, analytical legal method and descriptive legal method. As a result, it was evidenced that the configuration of the negative administrative silence in the Ecuadorian legislation (COA), from the tacit refusals. Likewise, it was determined that, when the negative administrative silence is configured, it generates a violation of the basic guarantees of the right to due process, in which several effects are generated, among which it makes it feasible for the petitioner to resort to the administrative litigation, violates the legal security, as well as places him in a level of subordination to the administered.